Tinjuan Historis: Konformitas Pasar Tradisional versus Konsep Global Pembangunan Dunia - Achidsti, Sayfa Auliya (UI Scholars Hub, 2011)
The world has experienced many developments of each economic model. The interesting thing is that, the world wide economic development tend to be a linear development. If we seeon the past, e.g. several centuries ago, the economy in the world is all on the pure form of trading. Every area, with its own communities, has different natural resources and their own made-craft. Because of the difference in the community and natural resources each area has, it results on the commodity differentiation. It can not be denied that as the time goes by, human's needs will also develop not only in the sense of housing, clothes, and food needs but it is beyond those needs. The needs for other things and the eminence of each area of its natural resources are the factors which are finally emerging the need of exchange by inter-individuals on each area and to other areas. This is what we called as trading, in advance. By the existence of this kind of trading and the certainty of place and system, these result on the existence of what we call now as market. In the modernity context, what is explained as market here is a traditional market. The question is the existence of traditional market still relevant in the daily economic model, in which nowadays we are not in the peak time of traditional market anymore? Trading model which has capital source and orientation is being the focus of today's economy.